Sosialisasi Pembuatan Surat Melalui Layanan WAKEPO yang Terintegrasi dengan e-Office Desa di Desa Ranggon - Agung Nurrahman; Vira Wirna; Garryko Samosir (Civitas Consecratio: Journal of Community Service and Empowerment, 2023)
The background for the community service activities is the WAKEPO service which is integrated with the e-office in Ranggon Village. WAKEPO is a service that provides WhatsApp-based letter writing services that is integrated with the Village E-office. This service activity was carried out with the aim of knowing the extent of the knowledge of the people of Ranggon Village regarding the service of making administrative letters through WAKEPO. This service activity is carried out through a research and study-based approach. The author uses a quasi-experimental design with the one group pretest-posttest design (pre-posttest design in one group), where all respondents are given intervention or socialization without a group comparison. The target for community service activities is the Ranggon Village community with a total of 30 people. The result of the service activities carried out is that there is an influence of socialization on increasing public knowledge about making letters through the WAKEPO service. This increase can be seen from the mean value of 1.13 before the socialization and after the implementation of the socialization increased by 2.50. And from the results from Sig. (2-tailed) of 0.000. In conclusion, socialization activities for the people of Ranggon Village regarding the utilization of WAKEPO services need to be carried out periodically, in stages and continuously. The author recommends that the Ranggon Village Government be able to collaborate with the youth community of Ranggon Village in participating in encouraging changes in the mindset of the old generation so that they can adapt to technological changes.